DESENTRALISASI DAN OTONOMI DAERAH SEBAGAI UPAYA MEMAJUKAN KESEJAHTERAAN UMUM - Damanhuri Damanhuri (JPsd (Jurnal Pendidikan Sekolah Dasar), 2015)
The regional administration is realized through service improvement, empowerment and participation of the community in order to improve national and regional competitiveness with memperrhatikan democratic principles of justice and equity by taking into account the peculiarities of which is owned by an area in the frame of the Republic of Indonesia. Decentralization and regional autonomy will succeed if the infrastructure in the form of infrastructure, human resources and their effective legislation and the high participation of the community in an autonomous region. The implementation of regional autonomy with decentralization, deconcentration and perbantuan principle is expected to accelerate and facilitate the region to promote their respective regions on the initiative, initiative and creativity of each region. Without readiness mature and active participation in the local community, the regional autonomy it will be a problem for local communities.Keywords: Decentralization, Regional autonomy,  Commonweal